دور وكالات التصنيف الائتماني في حساب معدل كفاية رأس المال وفقا لمتطلبات لجنة بازل - زرقان, سهام; دربوش, محمد الطاهر (جامعة الوادي - University of Eloued, 2017)
يمثل موضوع كفاية رأس المال من أهم المواضيع على الساحة المصرفية لذلك تسعى السلطات الرقابية إلى البحث عن أفضل الطرق لحساب الحجم الأمثل لرأس المال الذي يجب الاحتفاظ به على مستوى البنوك لتغطية المخاطر، ومن أهم اللجان التي اهتمت بمعيار كفاية رأس المال لجنة بازل، وقد تطورت عملية حسابه وفقا لهذه اللجنة تبعا للتطورات الاقتصادية وذلك من خلال التعديلات التي شهدتها منذ إنشائها، ومن أهم ما جاءت به في هذا المجال الاعتماد على وكالات التصنيف في عملية تحديد الحد الأدنى لرأس المال، ويعتمد هذا الأسلوب على درجات التصنيف التي تقدمها هذه الوكالات. The control authorities strive to achieve the best possible means to determine the appropriate volume of the capital that should be kept at the level of banking in order to cover risks among the most important panels which are interested in the criteria of capital adequacy we may mention the basle committee. The issue of capital adequacy accounts has developed according to the need of basle committee following the economic development, through the witnessed adjustments since it creation. Among the main issues in the field of capital adequacy account the reliance on the agencies of credit in the field of determining the lowest level of capital. That method depends on the degrees of the credit classification which is provided by the credit rating agencies.
The role of credit ratings in the basel capital adequacy proposals
مقال
Keywords: وكالات تصنيف الائتمان، لجنة بازل، كفاية رأس المال; credit rating agencies, basle committee, capital adequacy